Youth and sustainable consumption: understanding awareness and adoption trends - BUZDUGAN Adriana; NEPOTU Lucia (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Purpose of the article: The article's goal is to examine young adults' awareness and adoption of sustainable consumption practises. Methodology: A national-level online survey of young adults aged 18 to 30 was used for the study. The survey included 20 questions about respondents' awareness, preferences, and sustainable consumption practises. Data was gathered and analysed in order to assess the level of awareness and adoption of sustainable consumption practises, as well as to validate hypotheses related to these factors. Conclusions: The findings show that the majority of young participants are aware of environmental issues and eager to adopt sustainable consumption habits. There were, however, significant differences in their behaviour, which could be influenced by factors such as age and educational level. Education and awareness campaigns, as well as providing diverse options and promoting flexitarian diets, can all help to encourage young adults to live a more sustainable lifestyle. Originality: From a national viewpoint, this study provides an important addition by providing current and representative data on the level of knowledge and implementation of sustainable consumption practises among young adults. It also gives practical suggestions for encouraging more responsible consumption within this age group, which has important environmental effects.